Perioperative nutrition: Recommendations from the ESPEN expert group. Issue 11 (November 2020) - Lobo, Dileep N.; Gianotti, Luca; Adiamah, Alfred; Barazzoni, Rocco; Deutz, Nicolaas E.P.; Dhatariya, Ketan; Greenhaff, Paul L.; Hiesmayr, Michael; Hjort Jakobsen, Dorthe; Klek, Stanislaw; Krznaric, Zeljko; Ljungqvist, Olle; et al.
Summary: Background & aims: Malnutrition has been recognized as a major risk factor for adverse postoperative outcomes. The ESPEN Symposium on perioperative nutrition was held in Nottingham, UK, on 14–15 October 2018 and the aims of this document were to highlight the scientific basis for the nutritional and metabolic management of surgical patients. Methods: This paper represents the opinion of experts in this multidisciplinary field and those of a patient and caregiver, based on current evidence. It highlights the current state of the art. Results: Surgical patients may present with varying degrees of malnutrition, sarcopenia, cachexia, obesity and myosteatosis. Preoperative optimization can help improve outcomes. Perioperative fluid therapy should aim at keeping the patient in as near zero fluid and electrolyte balance as possible. Similarly, glycemic control is especially important in those patients with poorly controlled diabetes, with a stepwise increase in the risk of infectious complications and mortality per increasing HbA1c. Immobilization can induce a decline in basal energy expenditure, reduced insulin sensitivity, anabolic resistance to protein nutrition and muscle strength, all of which impair clinical outcomes. There is a role for pharmaconutrition, pre-, pro- and syn-biotics, with the evidence being stronger in those undergoing surgery for gastrointestinal cancer. Conclusions: Nutritional assessment of the surgical patient together with the appropriate interventions to restore the energy deficit, avoid weight loss, preserve the gut microbiome and improve functional performance are all necessary components of the nutritional, metabolic and functional conditioning of the surgical patient.